The price elasticity of the demand and revenue increase for some Mexican planting seeds - Orozco Cirilo, Sergio; Vargas Canales, Juan Manuel; Medina Cuéllar, Sergio Ernesto; García Melchor, Nicasio (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2021)
The study of the price elasticity of demand (PED) has been and is a current research topic, as it greatly helps the managers of companies to make decisions about the price of their products and the expected repercussions in changing them. The objective of this study was to estimate PED and its impacts on the variation of income (VI) of six planting seed crops from Mexico, such as yellow corn, other corn (except yellow and sweet corn), sorghum, chickpea, pumpkin and cucumber. The data were gathering from the Foreign Agriculture Service (FAS) (1998-2018 period) through the tables provided and published on the Internet (secondary data). In this study, the arc method was applied to calculate PED and VI = ((Pf * Qf * 100) / (Pi * Qi)) - 100. Five of six the planting seed products have a relatively elastic demand price in most of the years, on the contrary the revenue increase had positive and negative values, without a defined trend. Sorghum planting seed has in some cases elastic demand and in other inelastic demand. It is concluded that there are no clear effects of the PED on the sales revenue of the aforementioned products; an aspect that contradicts the theory of PED and its impact on income.